The participation gap social status and political inequality - Dalton, Russell J. (Oxford, United Kingdom Oxford University Press, 2017)
The dilemma of democracy arises from two contrasting trends. More people in the established democracies are participating in civil society activity, contacting government officials, protesting, and using online activism and other creative forms of participation. At the same time, the importance of social status as an influence on political activity is increasing. The democratic principle of the equality of voice is eroding. The politically rich are getting richer-and the politically needy have less voice. This book assembles an unprecedented set of international public opinion surveys to identify the individual, institutional, and political factors that produce these trends. New forms of activity place greater demands on participants, raising the importance of social status skills and resources. Civil society activity further widens the participation gap. New norms of citizenship shift how people participate. And generational change and new online forms of activism accentuate this process. Effective and representative government requires a participatory citizenry and equal voice, and participation trends are undermining these outcomes. The Participation Gap both documents the growing participation gap in contemporary democracies and suggests ways that we can better achieve their theoretical ideal of a participatory citizenry and equal voice -- Provided by publisher
Political equality as the foundation of democracy -- Opening political doors -- For richer or poorer, politically speaking -- Civil society mobilizing action -- Age, generations, and participation -- What's a good citizen to do? -- The special case of online activism -- Contextual and inequality / Russell J. Dalton and Steve Weldon -- Is the gap widening? -- The political leanings of the choir -- Democracy in unequal terms -- Appendix : Survey Question Wordings -- Index.
Includes bibliographical references and index.
Keywords: Political participation; Democracy; Equality